THE USE OF ROLE PLAYING METHODS IN IMPROVING SPEAKING SKILLS KRAMA JAVA LANGUAGE IN GRADE V SD - Wafa, Hakimul; Wafa, Hakimul (KALAM CENDEKIA PGSD KEBUMEN, 2018)
The use of Role Playing Methods in Improving Speaking Skills Krama Java language in Grade V SD. This study aims to improve the skills of the Java language spoken manners inggil in fifth grade elementary school students with role playing method. This study is a collaborative action research conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. The subjects were students. The data of this study came from students, teachers, and observers. Data collection tool used was observation, interview guides and test speaking skills. These results indicate that the method can improve the skills Role Playing speak Javanese manners inggil in fifth grade elementary school students.